KORPRI housing development in Salatiga City: Backlog, problems and sustainability. Issue 1 (February 2020) - Sunarti,; Yuliastuti, N; Tyas, W P; Sari, D P P
Abstract: Housing backlog is a difficult problem to deal with, especially for low income communities. A way to reduce home ownership backlog in Salatiga City is the development of housing for KORPRI members, but now the ownerships and functions have changed. Based on these problems, the purpose of this study is to examine the development of KORPRI housing in Salatiga City with its problems and sustainability. The analysis technique is descriptive quantitative using data collected by distributing questionnaires to 40 households randomly and field observations of houses, its facilities and infrastructure. The results showed that low-cost housing development programs for civil servants of KORPRI members in Salatiga City had changed ownership of 62.5% to other people who were not low-income people and did not help reduce the backlog. The mechanisms and initial commitments were violated a lot by civil servants, who were the buyers, leaving many problems. The sustainability of housing development for KOPRI members that used government-owned land assets is to reduce the occupancy backlog, not the ownership backlog, i.e. houses with usufructuary rights.